Quality evaluation of flat layouts based on morphological, topological and geometric attributes that have implications in construction rationalization - Brandão, Douglas Queiroz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents the results of a research study which aimed to devise a method for assessing spatial arrangements of flats, considering attributes related both to the user needs and to construction rationalization. This study can be justified by the fact that most typical flat layouts do not offer a high level of comfort and quality for the final user, neither result in high degree of constructability. The variables related to the vertical plans, which correspond to 45% of building costs, were emphasized. This included the analysis of three attributes that affect the construction rationality: wall density, number of wall segments, and number of wall double junctions. A sample of 83 flat layouts with private areas of roughly 90 square metres (968.75 square feet), from 27 different Brazilian towns, was analysed. Some basic architectural characteristics were collected as well as some morphological and topological attributes, aiming to assess their impact on the use of materials and on construction rationalization. In conclusion, the study revealed that simple layouts that result in easier and faster site construction can also provide fairly comfortable and functional arrangements.